THE IMPLEMENTATION OF PROJECT-BASED LEARNING ON KOLINTANG MUSIC LEARNING - Yubal Johan Sebastian Banua; Glenie Latuni; Meyny Kaunang (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This study aims to describe the use of Project Based Learning (PjBL) in teaching Kolintang music at the junior high school level, with a focus on SMP Negeri 4 Tondano. Qualitative approach and musicological study were used by the researcher in this study, with data collection techniques through observations, interviews, and written notes. The results showed that cultural arts teachers at SMP Negeri 4 consistently apply learning models to improve students' academic achievement. Learning is conducted in three stages: preparation, core activities, and closing. In teaching Kolintang music, teachers use a project-based learning model with the following steps: 1) setting important questions; 2) planning project action steps; 3) making plans; 4) conducting evaluations; and 5) reflecting on past events. Students are guided towards higher order thinking through the Project Based Learning approach, and they are able to create 21st century learning products with positive results.